Third Five-Year Plan of Mysore District - Planning Commission (Planning Commission, 1959)
The District has always been the pivot of the structure of the administrations. The Mysore District has been divided into two Sub-Divisions comprising Mysore, Hunsur, Periyapatna, Krishnarajanagar, Heggadadevanakote Taluk as Mysore Sub-Division and Nanjangud, Gundlupet, Chamarajanagar, Yelandur, Kollegal and T. Narasipur Taluks as Nanjangud Sub-Divisions. After the reorganisation of States and with the inclusion of Kollegal Taluk which was formerly a part of Coimbatore District of the erstwhile Madras State, the Mysore District now consists of 11 Taluks with 49 Hobalies and 1,821 villages.
Government of Mysore